2019
DOI: 10.1021/acssuschemeng.9b01163
|View full text |Cite
|
Sign up to set email alerts
|

A Mussel Mimetic, Bioadhesive, Antimicrobial Patch Based on Dopamine-Modified Bacterial Cellulose/rGO/Ag NPs: A Green Approach toward Wound-Healing Applications

Abstract: A mussel mimetic transdermal patch was prepared using bacterial cellulose (BC), a green resource derived from Glucanoacetobacter xylinus (MTCC7795). To impart the mussel mimetic property, dopamine (DOPA), a catechol-containing compound, was used to modify the isolated BC via an amidation reaction between the carboxylated BC and DOPA, and the end product was successively characterized by 1H NMR and FTIR analysis. The free hydroxyl group of the DOPA moiety of DOPA-modified BC (BC-DOPA) was utilized to prepare BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 69 publications
0
45
0
Order By: Relevance
“…As shown in Fig. 2, compared with CA, the spectra of CA-2, 3-DA generated some new peaks at 7.10 and 2.53 ppm, which were the characteristic triplet peaks of the benzene ring and the methylene peak in the dopamine structure, respectively (Khamrai et al 2019;Zhong et al 2019). Combined with FTIR and 1 H NMR characterizations, it was confirmed that CA was successfully modified by dopamine.…”
Section: Resultsmentioning
confidence: 73%
“…As shown in Fig. 2, compared with CA, the spectra of CA-2, 3-DA generated some new peaks at 7.10 and 2.53 ppm, which were the characteristic triplet peaks of the benzene ring and the methylene peak in the dopamine structure, respectively (Khamrai et al 2019;Zhong et al 2019). Combined with FTIR and 1 H NMR characterizations, it was confirmed that CA was successfully modified by dopamine.…”
Section: Resultsmentioning
confidence: 73%
“…Another study by Khamrai et al focused on obtaining a mussel mimetic, antibacterial wound healing transdermal patch system by grafting dopamine onto the surface of carboxymethylated bacterial cellulose through an amidation reaction and further reducing Ag + and graphene oxide to obtain composite films. The composite films proved bactericidal properties and biocompatibility towards fibroblast cells and human lung epithelial cells, as well as the potential for wound healing owing to the acceleration of cell proliferation and migration [ 146 ]. Additionally, Limaye et al obtained cellulose nanofiber and polyvinyl alcohol-based films impregnated with AgNPs for antibacterial applications against B. subtilis and E. coli bacterial strains [ 147 ].…”
Section: Inorganic Nanoparticle-based Composite Films For Antimicrobial Applicationsmentioning
confidence: 99%
“…[ 111 ] Under external ES, the scaffold dressing exhibits high bioactivity, supporting myoblast adhesion and strengthening cell responses, further enhancing wound healing ( Table 5 ). [ 110,112–123 ] Another series of conductive hydrogels that are based on dopamine‐grafted hyaluronic acid and polydopamine‐coated reduced graphene oxide (rGO), which are crosslinked by oxidative coupling of catechol groups using an H 2 O 2 /horseradish peroxidase catalytic system, have been prepared as materials for dressing wounds (Figure 6b). [ 115 ] The as‐prepared composite hydrogels have adhesive, hemostatic, and antioxidant properties as well as mechanical properties that are similar to those of human skin.…”
Section: Electroactive Wound Dressings That Incorporate Inorganic Conmentioning
confidence: 99%